PENGEMBANGAN MEDIA SCRAPBOOK MATERI DAUR HIDUP HEWAN UNTUK PEMBELAJARAN IPA PADA PESERTA DIDIK KELAS IV SDN 41 INPRES PAMINGGALAN KABUPATEN MAJENE - Hardia; Hamzah Pagarra; Faidah Yusuf (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aimed to develop scrapbook-based learning media on animal life cycle material and to determine its validity and practicality in elementary science learning. The research employed a Research and Development (R&D) approach using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. Data were collected through validation questionnaires completed by material experts and media experts, as well as practicality questionnaires from teachers and students. The results showed that the scrapbook media was valid and practical. Material expert validation reached 81.66%, while media expert validation reached 85%. The practicality test showed a teacher response of 100% and a student response of 97%, both categorized as very practical. These findings indicate that scrapbook media is suitable to support science learning on animal life cycle concepts in elementary school.